Gestes et images du voyage en Orient - Monique Sicard (Flaubert: Revue Critique et Génétique)
It has often been said that Flaubert rejected photography. We wish to review this statement by studying what photographs Flaubert saw during his eighteen-month-long trip in the Orient. Indeed, he closely witnessed the complex gestures and production of paper negatives, beautiful photographic objects whose novelty cannot have left him indifferent. In fact, the presence of photography in his letters and his travel notebooks is more important than it might first appear. These large negatives, that result in a symbolic and effective link with the book, are not to be confused with the use of photo-cards that later led Flaubert to reject photographic objects. This article shows the contribution of the history of photography in the debate, and the necessity of favoring a diversity of photographic objects instead of the concept named, as a matter of convenience, “photography”.